# 9(13-x)-4x=5x(21-2x)+9x

## Simple and best practice solution for 9(13-x)-4x=5x(21-2x)+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 9(13-x)-4x=5x(21-2x)+9x equation:

9(13-x)-4x=5x(21-2x)+9x
We move all terms to the left:
9(13-x)-4x-(5x(21-2x)+9x)=0
We add all the numbers together, and all the variables
9(-1x+13)-4x-(5x(-2x+21)+9x)=0
We add all the numbers together, and all the variables
-4x+9(-1x+13)-(5x(-2x+21)+9x)=0
We multiply parentheses
-4x-9x-(5x(-2x+21)+9x)+117=0

We calculate terms in parentheses: -(5x(-2x+21)+9x), so:
5x(-2x+21)+9x
We add all the numbers together, and all the variables
9x+5x(-2x+21)
We multiply parentheses
-10x^2+9x+105x
We add all the numbers together, and all the variables
-10x^2+114x
Back to the equation:
-(-10x^2+114x)

We add all the numbers together, and all the variables
-(-10x^2+114x)-13x+117=0
We get rid of parentheses
10x^2-114x-13x+117=0
We add all the numbers together, and all the variables
10x^2-127x+117=0
a = 10; b = -127; c = +117;Δ = b2-4acΔ = -1272-4·10·117Δ = 11449The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{11449}=107$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-127)-107}{2*10}=\frac{20}{20} =1$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-127)+107}{2*10}=\frac{234}{20} =11+7/10$

`